NATIVE MINERALS AND INTERMETALLIDES OF NOBLE AND NONFERROUS METALS IN SEDIMENTS OF THE MARKOV DEEP, MID-ATLANTIC RIDGE - Bortnikov N.S.; Mochalov A.G.; Cherkashev G.A. (My University, 2006)
The study of modern mineralization in spreading zones of the World Ocean is mainly focused on the precipitation of minerals from hydrothermal fluids and the consequent formation of sulfide edifices. However, the study of ore minerals formed in the course of the alteration of magmatic rocks is no less essential. The present paper reports the first findings of native minerals of noble metals in sediments of the Markov Deep, Mid-Atlantic Ridge.